RELATIONSHIP BETWEEN LEARNING FACILITIES, LEARNING INTENSITY, AND SELF-CONFIDENCE WITH STUDENTS 'MATHEMATICS RESULTS OF CLASS VII MTs MUHAMMADIYAH KARANGKAJEN - Dwi Arimbi; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Low student learning outcomes are associated with many factors. Learning facilities, learning intensity, and self-confidence are some of the factors associated with learning outcomes. This study aims to determine whether or not a positive and significant relationship between learning facilities, learning intensity, and self-confidence results from learning mathematics students of class VII MTs Muhammadiyah Karangkajen Yogyakarta Semester Even In Academic Year    2016/2017. The population in this research was the students of VII grade in MTs Muhammadiyah Karangkajen Yogyakarta semester even in the academic year 2016/2017, consisted of class    VIIA, VIIB, VIIC, VIID, VIIE totaling 145 students. Trial class and sample class were taken by random sampling technique. They obtained trial class from VIIA and sample class from VII C. The writer uses a questionnaire method to collect the data of learning facilities, learning intensity learning, and self-confidence and test method to get the results of learning mathematics. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, linearity test, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between learning facilities, learning intensity, and self-confidence with the results of learning mathematics students class VII of MTs Muhammadiyah Karangkajen Yogyakarta semester even in academic year 2016/2017. It is showed by Fcount  Ftable is 3.1689 > 3.07 with R = 0.4864 and (R2) = 0.2365 with with Relative Contribution = , Relative Contribution    =  and Relative Contribution = , Effective Contribution = , Effective Contribution =  and Effective Contribution = .